Implementasi Etika Bisnis Islam Pedagang Muslim di Pasar Sentral Kota Medan - Fitrah Ilham Ramdhan; Waizul Qarni; Budi Harianto (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to depict and analyze the ethical practices of traders dealing in worship equipment at Sentral Pasar, Medan Kota District, Medan City, North Sumatra, considering the principles of Islamic business ethics. Methodology/approach: The research methodology employed is qualitative, utilizing a field research approach. The subjects of the study comprise worship equipment traders at Sentral Pasar, Medan Kota District, Medan City, North Sumatra. Data sources encompass both primary and secondary data, collected through interviews, observations, and documentation. Results/findings: The findings reveal that traders are proficient in applying the three aspects of Islamic business axioms-balance, free will, and responsibility-despite encountering several obstacles along the way. Limitations: Some limitations that may be encountered include challenges in changing established business behavior, limited resources for training and education, and resistance to change on the part of traders who may be comfortable with existing practices. Contribution: Increasing understanding of the importance of Islamic business ethics in trading, so that they can direct their trading businesses in accordance with Islamic rules and sharia.